Recent advances in active packaging of agri-food products: a review - Bhardwaj, Aastha; Alam, Tanweer; Talwar, Nishtha (Journal of Postharvest Technology, 2019)
Food products are vulnerable to biochemical spoilages and microbiological contamination through light, water vapour, oxygen and other outside environmental barriers, in spite of the upcoming barrier film technologies, preservation techniques and processing methods. Thus, there is a need for appropriate packaging technology to increase their shelf-life. Active packaging is increasingly becoming popular that can prove to be an indispensible vehicle in the preservation of food items as it provides barrier to external influences as well as preventing contamination inside the package. Active packaging can be defined as the inclusion of an active system into packaging film or a container to maintain the quality or extend the shelf life of the product. Major active packaging systems such as moisture controllers, oxygen scavengers, carbon dioxide emitters/absorbers, antioxidants, ethylene absorbers, flavor releasing/absorbing systems, antimicrobials etc. have been discussed and their mechanism of action along with their effect on the shelf life of foods has been briefly outlined in this article. Efforts have been made to review the past as well as recent researches along with its future perspectives through this article, w.r.t active packaging as an upcoming and novel preservation and packaging technique. Developments in nanotechnology will also enable the advances for a better and novel active and intelligent packaging.